Problems in Mythological Reconstruction: Thor, Thrym, and the Story of the Hammer over the Course of Time - Vijūnas, Aurelijus (Scandinavistica Vilnensis, 2019)
In this article, the Old Icelandic poem Þrymskviða, which depicts an ancient myth about the theft and retrieval of Thor’s hammer, is compared with a number of later texts describing the same story – a late medieval Icelandic rhyme Þrymlur and a number of ballads from Denmark, Norway, and Sweden, – in order to find out if it is possible to reconstruct an earlier, common Scandinavian version of this myth. While such a reconstruction appears to be plausible, none of the extant sources reflects the proto-myth in its complete form: although the oldest source Þrymskviða generally appears to be the most conservative among the different versions of this story, some of the scenes from the proto-myth have been preserved better in the later sources.